Hospital readmission prediction with long clinical notes - Nurmahomed, Yassin (Department of Computer Science, 2023)
Electronic health records (EHR) data is captured across many healthcare institutions, resulting in large amounts of diverse information that can be analysed for diagnosis, prognosis, treatment and prevention of disease. One type of data captured by EHRs are clinical notes, which are unstructured data written in natural language. We can leverage Natural Language Processing (NLP) to build machine learning (ML) models to gain understanding from clinical notes that will enable us to predict clinical outcomes. ClinicalBERT is a pre-trained Transformer based model which is trained on clinical text and is able to predict 30-day hospital readmission from clinical notes. Although the performance is good, it suffers from a limitation on the size of the text sequence that is fed as input to the model. Models using longer sequences have been shown to perform better on different ML tasks, even with clinical text. In this work, a ML model called Longformer which pre-trained then fine-tuned on clinical text and is able to learn from longer sequences than previous models is evaluated. Performance is evaluated against the Deep Averaging Network (DAN) and Long short-term memory (LSTM) baselines and previous state-of-the-art models in terms of Area under the receiver operating characteristic curve (AUROC), Area under the precision-recall curve (AUPRC) and Recall at precision of 70% (RP70). Longformer is able to best ClinicalBERT on two performance metrics, however it is not able to surpass one of the baselines in any of the metrics. Training the model on early notes did not result in substantial difference when compared to training on discharge summaries. Our analysis shows that the model suffers from out-of-vocabulary words, as many biomedical concepts are missing from the original pre-training corpus.